2014
DOI: 10.1128/aem.00004-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Phenotypic Responses of Listeria monocytogenes to Chlorine Dioxide

Abstract: Significant food-borne disease outbreaks have occurred from consumption of ready-to-eat foods, including produce, contaminated with Listeria monocytogenes. Challenging food matrices (e.g., cantaloupe, sprouts) with limited processing steps postharvest to reduce pathogen loads have underscored a need for new mitigation strategies. Chlorine dioxide (ClO 2 ) is increasingly being used in produce and other food systems to reduce food-borne pathogen levels. The goal of this study was to characterize the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
0
23
1
Order By: Relevance
“…Although other studies observed pronounced transcriptional shifts (Pleitner et al, 2014) and increased expression of a functionally characterized oxidative stress survival islet (Harter et al, 2017) following 15 and 10 min exposures to oxidative stress, respectively, our study observed relatively minor transcriptomic differences even after 30 min of oxidative stress exposure. Only nine DE genes were seen in the R479a hydrogen peroxide treatment ( Supplementary Table S3), although seven of these were also among the 50 DE genes of 6179 with the highest log2fold changes (Supplementary Table S4).…”
Section: Chromosomal Gene Expression Changes In Response To Hydrogen contrasting
confidence: 94%
See 4 more Smart Citations
“…Although other studies observed pronounced transcriptional shifts (Pleitner et al, 2014) and increased expression of a functionally characterized oxidative stress survival islet (Harter et al, 2017) following 15 and 10 min exposures to oxidative stress, respectively, our study observed relatively minor transcriptomic differences even after 30 min of oxidative stress exposure. Only nine DE genes were seen in the R479a hydrogen peroxide treatment ( Supplementary Table S3), although seven of these were also among the 50 DE genes of 6179 with the highest log2fold changes (Supplementary Table S4).…”
Section: Chromosomal Gene Expression Changes In Response To Hydrogen contrasting
confidence: 94%
“…These studies also showed that lmo2230 is upregulated during early stationary phase (Raengpradub et al, 2008;Oliver et al, 2009), within the murine intestinal lumen (Toledo-Arana et al, 2009) and in response to osmotic and acid stress (Raengpradub et al, 2008;Utratna et al, 2011;Horlbog et al, 2019). Heat and cold stress have also been shown to induce lmo2230 expression (van der Veen et al, 2007;Hingston et al, 2017a), and lmo2230 is also upregulated after chlorine dioxide exposure (Pleitner et al, 2014).…”
Section: σ B Genesmentioning
confidence: 83%
See 3 more Smart Citations